2022
DOI: 10.3389/fmicb.2022.972777
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and unignorable extragastric diseases: Mechanism and implications

Abstract: Considered as the most popular pathogen worldwide, Helicobacter pylori is intensively associated with diverse gastric diseases, including gastric ulcers, chronic progressive gastritis, and gastric cancer. Aside from its pathogenic effect on gastric diseases, growing evidences reveal that H. pylori may be related to numerous extragastric diseases. In this article, we reviewed recent studies and systematically elucidated that H. pylori may interfere with many biological processes outside the stomach and influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 124 publications
0
16
0
Order By: Relevance
“…Based on the fact that a chronic untreated H. pylori infection may induce systemic effects and contribute to tissue damage in distant sites from the stomach, such as the lungs (the respiratory and the digestive tract share a common embryological origin), researchers believe that more efforts are necessary to understand the pathophysiological pathways involved [ 45 ]. To make things even more complicated, many epidemiological studies have reported on a possible pathogenetical role of H. pylori in extragastric diseases via a potential relation to chronic systemic inflammation and molecular mimicry [ 46 ]. Furthermore, the recent context of COVID-19 has renewed the interest of pathologists in diseases of infectious origin [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that a chronic untreated H. pylori infection may induce systemic effects and contribute to tissue damage in distant sites from the stomach, such as the lungs (the respiratory and the digestive tract share a common embryological origin), researchers believe that more efforts are necessary to understand the pathophysiological pathways involved [ 45 ]. To make things even more complicated, many epidemiological studies have reported on a possible pathogenetical role of H. pylori in extragastric diseases via a potential relation to chronic systemic inflammation and molecular mimicry [ 46 ]. Furthermore, the recent context of COVID-19 has renewed the interest of pathologists in diseases of infectious origin [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, numerous H. pylori-related guidelines recommend the national eradication of H. pylori; yet, there are still many countries that are under great pressure on public health, and eradicating H. pylori nationally may pose a potential risk of antibiotic abuse (Kato et al, 2019;Jung et al, 2021;National Clinical Research Center for Digestive Diseases (Shanghai) et al, 2021). Eradicating H. pylori infection is still controversial in inflammatory bowel disease, gastroesophageal reflux disease, asthma, and other diseases (He et al, 2022). Moreover, the benefits and risks of eradicating H. pylori vary among individuals…”
Section: Discussionmentioning
confidence: 99%
“…This link is believed to originate from H. pylori-induced chronic gastritis, leading to gastric mucosal damage and occult blood loss, resulting in iron de ciency and IDA 9 . Additionally, Sarari et al reported vitamin B12 de ciency in 67.4% of H. pylori-infected patients 10 , likely due to gastritis-induced atrophic changes in the gastric mucosa, impairing vitamin B12 absorption 11 . These associations, while supported by epidemiological data, remain speculative due to observational studies' limitations, such as confounding variables and inability to establish causality.…”
Section: Introductionmentioning
confidence: 99%